Anomalies in groundwater composition caused by earthquakes: examples and modeling issues - Kopylova G.N.; Boldina S.V. (E3S Web of Conferences, 2019)
The examples of modeling hydrogeochemical anomalies recorded in the observation wells and sources of Kamchatka caused by the preparation of strong local earthquakes and the impact of seismic waves are considered. As a working hypothesis explaining the formation of such anomalies, assumptions about the change of conditions (1) of mixing of two waters, contrasting in chemical composition and (2) interaction in the «water – rock» system are used.